Rewritten in vertex form please!!! Asap!!!
![Rewritten in vertex form please Asap class=](https://us-static.z-dn.net/files/dd0/cd8db511ff7680323cedd96bf1323cfb.png)
Answer:
vertex form: [tex]y=2(x+\dfrac{7}{2})^2+\dfrac{1}{2}[/tex]
B correct
Step-by-step explanation:
[tex]y=(x+3)^2+(x+4)^2[/tex]
[tex]y=x^2+9+6x+x^2+16+8x[/tex]
[tex]y=2x^2+14x+25[/tex]
[tex]y=2(x^2+7x)+25[/tex]
[tex]y=2(x^2+7x+\dfrac{49}{4}-\dfrac{49}{4})+25[/tex]
[tex]y=2(x+\dfrac{7}{2})^2+\dfrac{1}{2}[/tex]
Answer:
B
Step-by-step explanation:
The equation of a parabola in vertex form is
y = a(x - h)² + k
where (h, k) are the coordinates of the vertex and a is a multiplier
Given
y = (x + 3)² + (x + 4)² ← expand and simplify
= x² + 6x + 9 + x² + 8x + 16
= 2x² + 14x + 25
To obtain vertex form use the method of completing the square
The coefficient of the x² term must be 1
Factor out 2 from 2x² + 14x
y = 2(x² + 7x) + 25
add/ subtract ( half the coefficient of the x- term )² to x² + 7x
y = 2(x² + 2([tex]\frac{7}{2}[/tex]) x + [tex]\frac{49}{4}[/tex] - [tex]\frac{49}{4}[/tex] ) + 25
y = 2(x + [tex]\frac{7}{2}[/tex] )² - [tex]\frac{49}{2}[/tex] + [tex]\frac{50}{2}[/tex]
y = 2(x + [tex]\frac{7}{2}[/tex] )² + [tex]\frac{1}{2}[/tex]